THE IMPACT OF COVID-19 PANDEMIC ON TOURISM DEVELOPMENT IN WESTERN BALKAN COUNTRIES - Radukić, Snežana; Petrović-Ranđelović, Marija; Petrović, Jelena (Horizons - International Scientific Journal, 2022)
The COVID-19 pandemic is the cause of the global health crisis, economic downturn and financial crisis. The tourism was the most affected industry because moving and travel restrictions put in place. The purpose of this paper is to analyze the impact of COVID-19 on tourism development in Western Balkan countries. The aim of this paper is to analyze whether it exists the difference impact of COVID-19 on tourism development of Western Balkan countries. The results of research indicate that COVID-19 was the most important impact on tourism development of observed countries during this century. In 2020, the Western Balkan countries recorded the decrease of number of foreign tourists and tourism receipts, but the same time recorded the increase of receipts per tourist. At the same time, the results indicate that tourism and death rate have significant impact on the economic growth of Western Balkan countries.